2010
DOI: 10.1080/08853908.2010.491419
|View full text |Cite
|
Sign up to set email alerts
|

Trade in Services: The Elasticity Approach for The Case of Turkey

Abstract: This study includes the analysis of global trade in the services

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
2
2
Order By: Relevance
“…Strong support was found for the conclusion that the short-run exchange rates do not play a very important role in the long-run behavior of import and export demand. This is in contrast to studies on export and import demand functions for services, where for example Ketenci and Uz (2010) found that short-run exchange rate elasticities of export and the import of services are highly elastic compared with inelastic long-run exchange rate elasticities in Turkey. In all countries, the short run exchange rate elasticities in export and import demand functions were found highly inelastic, nearly zero.…”
Section: Error Correction Modelcontrasting
confidence: 96%
“…Strong support was found for the conclusion that the short-run exchange rates do not play a very important role in the long-run behavior of import and export demand. This is in contrast to studies on export and import demand functions for services, where for example Ketenci and Uz (2010) found that short-run exchange rate elasticities of export and the import of services are highly elastic compared with inelastic long-run exchange rate elasticities in Turkey. In all countries, the short run exchange rate elasticities in export and import demand functions were found highly inelastic, nearly zero.…”
Section: Error Correction Modelcontrasting
confidence: 96%
“…That is, 1(1), which implies the existence of unit root. This is consistent with the findings of Ketenci and Uz (2010). .rrcm tne Johansen cointegration test results represented in table 10, we found strong evidence of the cointegrating reiatior.sni.…”
Section: Estimating Price and Income Elasticities Of Trade In Service...supporting
confidence: 93%
“…We found strong evidence of positive values for income elasticities. Additionally, in contrast to Ketenci and Uz (2010), we found that income elasticity for export is significantly greater than income elasticity for import of services.…”
Section: Icontrasting
confidence: 87%
See 1 more Smart Citation
“…Employing a VAR model to investigate the exchange rate propagation mechanisms to real exports of U.S. services and agricultural sectors on monthly data from 1992:1 to 2009:12, Ojede (2015) found that exchange rate shocks impact services exports more than they do on agricultural exports. However, Ketenci and Uz (2010) empirical findings revealed that the real exchange rate is not a significant determinant for the trade in services. Other studies such as Prieto et al (2011) revealed that internet penetration is a significant determinant of trade in services in the importing country as opposed to the exporter.…”
Section: Empirical Literature On Trade In Services and Exchange Ratementioning
confidence: 90%